Aspek Ekologi dalam Kumpulan Puisi Setelah Gelanggang Itu Karya Esha Tegar Putra: Tinjauan Ekologi Sastra - Silfia Febriani; Iswadi Bahardur; Armet (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This study aims to find out the problems of cultural ecology that are depicted in the collection of poems After the Arena by Esha Tegar Putra. To find out the description of these problems, this research method is a qualitative research using a descriptive analysis approach. The data in this study are excerpts of poetic texts in the form of words, phrases, sentences in the array and stanza units of each poem in the collection After the Arena by Esha Tegar Putra. Based on the analysis of the data, it can be concluded three things. First, the link between technology, production or exploitation of resources and the environment. Second, the pattern of community action in exploiting and producing resources using the technology they have. Third, patterns of behavior in society that affect other cultural aspects such as; Value systems, belief systems and religious systems.